Proposta de controle em malha fechada com alta fficiência para o aquecimento de água em chuveiros elétricos - Bernardo, Marcos Gomes (2014)
The present work deals with the analysis and development of a closed-loop system for the effective control of water temperature on the output of an electric shower, independently of both the water flow or water temperature at its entrance. The system targets low cost, small physical dimensions and high efficiency. The goal is a system with physical dimensions small enough to be directly incorporated into existing electric showers, without the need for the manufacturer to reformulate their product. The high efficiency ends up being of paramount importance because it contributes effectively in both the size and cost of the solution: the lower the losses (greater efficiency) the smaller the heatsink needed, reducing the size and cost of the solution. Based on these criteria, we decided to use a TRIAC as a power switch and turning it on only at the zero crossings of the mains. For the design and development of the system, we adopted as tools Scilab and the Arduino platform. Prior to the assembly of the prototype, several simulations of circuits and programming codes were performed using the Proteus and Scilab together. For the experimental tests, a prototype with a nominal power of 3.2 kW was built employing a commercial electric shower. Experimentally, we obtained an efficiency greater than 99 %, which in turn required a heatsink with a volume of 63 cm³, and effective control of water temperature on the output device. Moreover, no noticeable flicker was observed when considering an electrical installation in accordance with Brazilian standards.